2021
DOI: 10.21037/apm-21-1405
|View full text |Cite
|
Sign up to set email alerts
|

Bedtime administration of antihypertensive medication can reduce morning blood pressure surges in hypertensive patients: a systematic review and meta-analysis

Abstract: Background: The risk of cardiovascular and cerebrovascular events is the highest during the first several hours post-awakening in patients with hypertension. This is largely due to surges in morning blood pressure (BP). The current meta-analysis explored whether morning BP is affected by the timing of antihypertensive drug administration.Methods: Four medical databases were searched for clinical trials that examined the relationship between the timing of antihypertensive drug administration and morning BP leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…adopted a chronotherapeutic protocol to treat NDH, which reduced blood pressure and effectively corrected the “non‐dipper” curve of blood pressure, with significant patient benefit. In a meta‐analysis, Jiang 26 et al. reported that bedtime administration of antihypertensive drugs reduced dSBP by 1.17 mmHg and cardiovascular‐related mortality by 2.1%.…”
Section: Discussionmentioning
confidence: 99%
“…adopted a chronotherapeutic protocol to treat NDH, which reduced blood pressure and effectively corrected the “non‐dipper” curve of blood pressure, with significant patient benefit. In a meta‐analysis, Jiang 26 et al. reported that bedtime administration of antihypertensive drugs reduced dSBP by 1.17 mmHg and cardiovascular‐related mortality by 2.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Still, we could not find a significant association of dipping patterns with E-selectin. The time of day when antihypertensive drugs are taken plays a significant role in nocturnal BP fall [ 62 ] and this might have influenced our results. Additionally, another explanation is the use of certain antihypertensive drugs such as long-acting calcium channel blockers and angiotensin II-receptor blockers which have been shown to decrease E-selectin levels [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…For EHT and MoEHT groups, the independently associated clinical factor was taking at least 1 long-acting antihypertensive drug once daily in the morning. Antihypertensive drugs were an important factor in home BP control since previous studies of chronotherapy of hypertension indicated that evening or bedtime administration of antihypertensive drugs improved morning BP control [36][37][38]. Because of the long duration of action of antihypertensive drugs that were taken in the morning, the evening home BP was controlled to achieve the BP target.…”
Section: Discussionmentioning
confidence: 99%